Evaluativity in even-hosting comparatives: Information structure and salient scales - Chen, Zhuang (Proceedings of the Amsterdam Colloquium, 2024)
Even-hosting comparatives trigger an evaluative inference that is absent in even-less coun terparts. Greenberg 2018 offers a degree-based account to formally explain this phenomenon, but this account is criticized by Bi 2022 for (i) failure to capture cases where even associates with the comparison target and, more fatally, (ii) running the risk of over-generation. Ar guing for the degree-based account, this work shows how it can systematically explain this phenomenon. More crucially, by offering a novel, information structure-based argument, we claim that this account is free of any over-generation risk, and further demonstrate how this novel perspective presents a simple account for cases involving negation. Thus, apart from addressing this phenomenon per se, this work sheds light on how information structure helps to constrain the choice of the salient scales with scalar, alternative-sensitive expressions.